DARI SIMULASI REALITAS SOSIAL HINGGA HIPER-REALITAS VISUAL: Tinjauan Komunikasi Virtual Melalui Sosial Media di Cyberspace - Yanti Dwi Astuti (Profetik: Jurnal Komunikasi, 2015)
In this postmodern era, technology has growing very rapidly so as to bring peoples into the digital world (cyberspace), a new space to present a virtual and provide free space for each individual to take any action which lasts reality simulation. The development of digital technology has brought the fantasy of man through the boundaries, creating spaces of the three following dimensions of objects in it, up to the stage where virtual reality has exceeded the manipulation of visual imagery so as man stepped from the real world to the fantasy world, the virtual world look real. Specifically, this paper will discuss how the phenomenon of virtual reality coupled with the tangible reality by reviewing the virtual communication through social media in cyberspace.The discussion will begin discussing the virtual communication through new media (internet), and on the establishment of the identity of identity both real and virtual identities. After that will be presented theory and hyper-reality simulation of Jean Baudrillard. the end of the discussion concluded that digitization in all areas such as a virus that slowly destroys human undetected, it offers the freedom and convenience of the virtual (pseudo) but behind it is actually a human being in hegemony, arranged and put into a structured system. then to minimize misperceptions, prejudices and misunderstandings we should establish a balanced communication link between the real world and the virtual world.